WANITA DALAM KEPEMIMPINAN DAN HUBUNGANNYA DENGAN KEMAJUAN PENDIDIKAN - Wahyuni, Imelda (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
Woman leadership has become one of the lively contemporary issues discussed, both in the view of theology, and sociology. The discussion is often associated with education. Education is the fulcrum of the effort to develop intellectual ability in order to achieve a specific purpose, such as the establishment of the leadership. The decades of women leadership since 1990 rise women leadership potential. The notion that women are not worthy to be a leader was undeniable by historical reality of women leadership. The influence of educational development toward women leadership can be seen if the mastery of science have impact on potential improvement, so that women leadership will be qualified if it is accompanied by strengthening of intelligence.